Analytical Liquid Chromatography New Perspectives - Moldoveanu, Serban C.; David, Victor (IntechOpen, 2022)
This book consists of several selected chapters on important subjects in modern high-performance liquid chromatography (HPLC) and ultra-performance liquid chromatography (UPLC). The content addresses aspects related to both improvements in the mainstream HPLC/UPLC technology and utilization, as well as developments of exploratory new materials and equipment. The book presents useful details about the presented subjects as well as describes new applications and/or relevant case studies for each subject. It is addressed to a large audience of analytical chemists involved in separation science. Each chapter is authored by scientists with considerable field and academic experience.